Antara Cita-cita Konservasi dan Kerentanan Masuk Sandera Eksploitasi (Kajian Atas Beberapa Judicial Review terhadap UU Kehutanan) - Faiq Tobroni (Jurnal Konstitusi, 2016)
This paper aims to discuss some decisions of the Constitutional Court on judicial review of the Forestry Law. There are both positive and negative. A positive decision, to my opinion, can seen in No 013/PUU-III/2005   and No 021/PUU-III/2005. The reason I regard as a positive is based on the consequences of decision, which legitimates article about the ban on illegal logging in forests and the confiscation of equipment for stealing wood as constitutional ones. It is supporting conservation.A decision that negatively affects the spirit of conservation is noted in decision No. 003/PUU-II/2005. This ruling tends to prioritize legal certainty for mining companies to resume an open mine system in the preserved forestry. The author saw this one as reflection  of  the  legal policy construction on forestry law that is taken hostage by exploitation interests.This paper, furthermore, tries to uncover the legal policy construction on forestry law as the base of problem sources. Therefore, the author needs to search for not only informations which are in the textual decision, but also ones are beyond it. The larger model of legal policy can be seen from the process of determining emergency condition when formulating the Stipulation of Government Regulation in Lieu of Law (Perpu), then when changing the Perpu become law, and government regulations concerning forestry post-decision of the Court Number   003/PUU-II/2005.The advantage of this paper is on efforts to uncover the source alignments of forestry law on the big corporation based on decision number 003/PUU-II/2005. It to know this source that could be an important basis to understand why decision of the Constitutional Court on the preserved forest is taken  hostage.